Best of DETAIL : Einfamilienhäuser / Single-Family Homes - Schittich, Christian (best of DETAIL, 2015)
Best of DETAIL: Single-Family Homes brings together a collection of relevant highlights from DETAIL. The publication is made up of theoretical articles and a comprehensive section containing examples of projects which provide unique insights into the various applications of wood, concrete or masonry in a range of passive houses, bungalows, double- and semi-detached houses, and villas with swimming pools, from the simple to the luxurious.